An updated look at the use of silver diamine fluoride in U.S. dental schools' predoctoral curriculum—a survey - Jakubauskas, Benas; Pagni, Sarah; Ferreira Zandona, Andrea G. (Frontiers in Dental Medicine, 2025)
This survey aimed to update Silver Diamine Fluoride (SDF) use/teaching in U.S. predoctoral dental education programs in comparison to a 2016 survey, considering the COVID-19 pandemic. An online survey via email was sent to all accredited U.S. predoctoral dental education programs (n=68) in January 2022. A total of 39 schools (57% response rate) responded to the survey, and all 39 of them reported that SDF was now part of their curriculum, significantly different (p<0.001) from 2016 (68% of schools). Significant changes (p<0.001) were reported in the survey responses from 2016 to 2022, particularly in how SDF was being taught (97 % teaching didactically and clinically versus 48% in 2016), but were not necessarily a response to the COVID pandemic. Schools report teaching more indications for the use of SDF and using more specific protocols with more schools teaching arresting caries in permanent teeth (97% versus 78% in 2016). Since 2016, the use and teaching of SDF have been increasingly adopted across U.S. dental schools, though there remains room for improvement in terms of consistent implementation, specific clinical protocols, and comprehensive training.